(Na, K)NbO3 nanoparticle-embedded piezoelectric nanofiber composites for flexible nanogenerators. (6th May 2015) - Kang, Han Byul; Han, Chan Su; Pyun, Jae Chul; Ryu, Won Hyoung; Kang, Chong-Yun; Cho, Yong Soo
Abstract: Piezoelectric composite nanofibers based on (Na0.5, K0.5 )NbO3 (NKN) nanoparticles embedded in poly(vinylidene fluoride–trifluoroethylene) [P(VDF–TrFE)] polymer are investigated in terms of their performance as nanogenerators. Perovskite NKN nanoparticles with ∼30–105 nm were separately prepared by combustion synthesis using polyacrylic acid (PAA) as a fuel. Surface modification of nanoparticles by tetradecylphosphonic acid (TDPA) was essential to secure proper adhesion with the polymer in the nanofibers prepared by electrospinning. Location-dependent piezoelectricity measurements confirmed that the region of embedded NKN filler particles exhibited better piezoelectricity than the P(VDF–TrFE) matrix region. Energy harvesting performance of the flexible composite nanogenerator demonstrated ∼0.98 V output voltage and ∼78 nA output current, which were enhanced depending on the volume fraction of the NKN nanoparticles dispersed in the polymer.